Interglial Crosstalk in Obesity-Induced Hypothalamic Inflammation - Rahman, Md Habibur; Kim, Min-Seon; Lee, In-Kyu; Yu, Rina; Suk, Kyoungho (Frontiers in Neuroscience, 2018)
Glial cells have recently gained particular attention for their close involvement in neuroinflammation and metabolic disorders including obesity and diabetes. Several signaling molecules and their receptors have been shown to be expressed by different types of glial cells resident in the central nervous system (CNS), and their crosstalks have been implicated in physiology and pathology of the CNS. Emerging evidence illustrates that malfunctioning glia and their products are an important component of hypothalamic inflammation. Recent studies have suggested that glia-glia crosstalk is a pivotal mechanism of overnutrition-induced chronic hypothalamic inflammation, which might be intrinsically associated with obesity/diabetes and their pathological consequences. In this review, we discuss the current advances in the molecular aspects of interglial crosstalk in hypothalamic inflammation, proposing a central role of such a crosstalk in the development of obesity, diabetes, and their complications. Finally, we explore the possibilities and challenges of targeting glial cells and their crosstalk for a better understanding of hypothalamic inflammation and related metabolic dysfunctions.